Rekayasa Otomatisasi Infrastruktur Jaringan Virtual Berbasis Open Vswitch Menggunakan Ansible pada Proxmox VE - Muhammad Wardhani; Muhammad Irfan; Hidayatunnisai Hidayatunnisai; Fidyah Ajeng Wulandari (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
Proxmox provides facilities for building private networks that enable each host to share physical resources through virtual networking, including Virtual Local Area Networks (VLANs). The Proxmox server supports Open vSwitch as a virtual switch, which is widely used among cloud developers to manage traffic between virtual machines and external communications. This study employs the Network Development Life Cycle (NDLC) method and the implementation of an automation engine based on Ansible to enhance the efficiency of virtual network configuration and reduce human errors. The testing results, based on five experimental scenarios, indicate that the automation system is capable of accelerating network creation operations by an average of 7 minutes and 43 seconds, network addition operations by an average of 7 minutes and 16 seconds, and network deletion operations by an average of 39 seconds compared to manual methods. These findings demonstrate that virtual network automation in Proxmox VE can significantly improve productivity and reliability in network management.